A method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone by mineral phase reconstruction and a magnesian natural hydraulic lime

CN122586405BActive Publication Date: 2026-10-27CHINA UNIV OF MINING & TECH (BEIJING)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610805251.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-10-27
Estimated Expiration
2046-06-05

AI Technical Summary

Technical Problem

[0004]有鉴于此,本发明提供了一种低品位镁质石灰石通过矿物相重构制备镁质天然水硬性石灰的方法与一种镁质天然水硬性石灰,以解决现有镁质石灰石直接制备天然水硬性石灰存在工艺复杂,成本高以及会削弱产品的“天然”属性的问题

Benefits of technology

1、本发明提供了一种基于“矿物相重构”策略,直接利用低品位镁质石灰石制备高性能镁质天然水硬性石灰的方法。本发明通过调控煅烧制度并引入复合矿化剂,将原料中的MgO从潜在的“有害相”重构为“有益矿物相”,从而从根源上解决安定性问题,并赋予材料优异的水硬性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application belongs to the technical field of building materials, and particularly discloses a method for preparing magnesian natural hydraulic lime by mineral phase reconstruction from low-grade magnesian limestone and the magnesian natural hydraulic lime. The application first mixes and grinds the crushed low-grade magnesian limestone with a composite mineralizer (borax: gypsum: nano titanium dioxide = 3-5: 5-7: 0.5-1), and then forms green bodies; then, the first calcination, the second calcination and the cooling step are performed to complete the mineral phase reconstruction, and the clinker is obtained; the clinker is subjected to normal temperature digestion and temperature rising digestion, and after digestion, the magnesian natural hydraulic lime is obtained through aging and grinding. The application directly uses the low-grade magnesian limestone to prepare the high-performance magnesian natural hydraulic lime based on the strategy of "mineral phase reconstruction", and the MgO in the raw material is reconstructed from the potential "harmful phase" to the "beneficial mineral phase", so that the stability problem is solved from the root, and the material is endowed with excellent hydraulic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to a method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone through mineral phase reconstruction, and a magnesian natural hydraulic lime. Background Technology

[0002] Natural hydraulic lime (NHL) has garnered significant attention due to its high compatibility with historic buildings and its environmental friendliness. Traditionally, this material is prepared from high-purity marl. However, in many regions, abundant low-grade limestone resources with high magnesium content are widely distributed. Because of their high dolomite content, this type of limestone readily forms magnesium oxide upon direct calcination. The slaking reaction of magnesium oxide is slow and difficult to complete, potentially leading to volume expansion and consequently poor material stability. Therefore, this resource has long been considered waste rock and has failed to achieve high-value utilization in the cementitious materials field.

[0003] While existing technologies include research on the preparation of hydraulic materials from magnesium raw materials, most involve chemical blending with added aluminosilicate raw materials (e.g., CN118479762A) or complex processes combining two-step calcination with high-pressure digestion (e.g., CN117361912A). These methods not only increase process complexity and production costs but also diminish the "natural" properties of the product to some extent. Therefore, developing a simple method for producing stable-performance magnesium-based natural hydraulic limestone directly from low-grade magnesium limestone has significant economic and social value. Summary of the Invention

[0004] In view of this, the present invention provides a method for preparing magnesian natural hydraulic limestone by mineral phase reconstruction from low-grade magnesian limestone and a magnesian natural hydraulic limestone, in order to solve the problems of complex process, high cost and weakening of the "natural" attribute of the product in the existing direct preparation of natural hydraulic limestone from magnesian limestone.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone through mineral phase reconstruction includes the following steps: 1) Crush low-grade magnesian limestone, mix and grind it with a composite mineralizer, and then mix it with water to form a raw material blank. 2) The raw material billet is subjected to the first calcination, the second calcination, and the cooling steps in sequence to complete the mineral phase reconstruction and obtain clinker; 3) After the clinker is crushed, it is sequentially digested at room temperature and then digested at elevated temperature to obtain the digested material; 4) The digested materials are sequentially aged and ground to obtain magnesian natural hydraulic lime; The composite mineralizer is obtained by mixing borax, gypsum and nano titanium dioxide in a mass ratio of 3~5:5~7:0.5~1.

[0006] Preferably, the chemical composition of the low-grade magnesian limestone, by mass percentage, is: CaO content 45~52%, MgO content 8~15%, SiO2 content 6~15%, calcination vector 27~35%, with the balance being impurities.

[0007] Preferably, the mass ratio of the low-grade magnesian limestone to the composite mineralizer in step 1) is 100:0.1~0.5.

[0008] Preferably, the specific surface area of ​​the low-grade magnesian limestone after grinding in step 1) is ≥400 m². 2 / kg; The particle size of the raw material blank is 2~5cm.

[0009] Preferably, in step 2), the temperature of the first calcination is 750~850℃, the time is 30~60min, and the heating rate is 5~8℃ / min; The second calcination temperature is 900~1000℃, the time is 60~120min, and the heating rate is 3~5℃ / min; The cooling rate of the cooling step is ≥50℃ / min.

[0010] Preferably, the room temperature digestion in step 3) is as follows: the crushed clinker is fed into the digestion reactor and water is sprayed for digestion; The particle size of the crushed clinker is ≤5mm; The mass of water injected during room temperature digestion is 15-30% of the total mass of MgO and CaO in the clinker.

[0011] Preferably, the heating digestion in step 3) is as follows: after the room temperature digestion is completed, the temperature of the digestion reactor is adjusted, water is sprayed first, and after the water spraying is completed, silica powder solution and citrate solution are sprayed in for digestion. In the heated digestion process, the temperature of the digestion reactor is 80~90℃; In the aforementioned heating and digestion process, the total mass of water used is 70-105% of the total mass of MgO and CaO in the clinker. The mass of water injected during the heated digestion process is 30-40% of the total mass of water used in the heated digestion process. In the heating digestion process, the mass ratio of clinker to silica powder in the silica powder solution and citrate in the citrate solution is 100:0.1~2:0.05~0.2.

[0012] Preferably, the relative humidity of the aging process is ≥90%, and the time is 24~48h; The specific surface area after grinding is 430~500m². 2 / kg.

[0013] Another object of the present invention is to provide a magnesium-based natural hydraulic lime prepared by the above preparation method.

[0014] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects: 1. This invention provides a method for preparing high-performance magnesian natural hydraulic limestone directly from low-grade magnesian limestone based on a "mineral phase reconstruction" strategy. By controlling the calcination process and introducing a composite mineralizer, this invention reconstructs MgO in the raw material from a potentially "harmful phase" into a "beneficial mineral phase," thereby fundamentally solving the stability problem and endowing the material with excellent hydraulic properties.

[0015] 2. This invention directly utilizes low-grade magnesian limestone, which is traditionally difficult to process, as the sole source of calcium, silicon, and magnesium. It eliminates the need for complex blending with high-purity silicon and aluminum raw materials, turning waste into treasure and yielding significant economic and environmental benefits.

[0016] 3. This invention uses the "mineral phase reconstruction" technology to transform harmful free MgO into beneficial mineral phases with hydraulic or filling effects, which not only completely solves the stability problem of magnesian lime, but also improves the pore structure and later strength enhancement rate of cement stone. Detailed Implementation

[0017] This invention provides a method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone through mineral phase reconstruction, comprising the following steps: 1) Crush low-grade magnesian limestone, mix and grind it with a composite mineralizer, and then mix it with water to form a raw material blank. 2) The raw material billet is subjected to the first calcination, the second calcination, and the cooling steps in sequence to complete the mineral phase reconstruction and obtain clinker; 3) After the clinker is crushed, it is sequentially digested at room temperature and then digested at elevated temperature to obtain the digested material; 4) The digested materials are aged and ground in sequence to obtain magnesium-based natural hydraulic lime.

[0018] In this invention, the chemical composition of the low-grade magnesian limestone, by mass percentage, is as follows: CaO content 45-52%, specifically 46%, 47%, 48%, 49%, 50%, 51%; MgO content 8-15%, specifically 10%, 12%, 14%; SiO2 content 6-15%, specifically 8%, 10%, 12%, 14%; ignition coefficient 27-35%, specifically 28%, 30%, 32%, 34%; balance impurities. The impurities include Al2O3 and Fe2O3, etc.

[0019] In this invention, the particle size after crushing is preferably 1~3mm, specifically 1.5mm, 2mm, or 2.5mm; the crushing is preferably performed by crushing and screening low-grade magnesian limestone ore to obtain magnesium-rich calcium powder with uniform composition.

[0020] In this invention, the mass ratio of low-grade magnesian limestone to composite mineralizer in step 1) is 100:0.1~0.5, preferably 100:0.2~0.4, and more preferably 100:0.3; the composite mineralizer is added in trace amounts.

[0021] In this invention, the composite mineralizer is obtained by mixing borax, gypsum and nano titanium dioxide in a mass ratio of 3~5:5~7:0.5~1, and the preferred mass ratio of the three is 3.4~4.5:5.5~6.5:0.6~0.9, and more preferably 4:6:0.8.

[0022] In this invention, the specific surface area of ​​the low-grade magnesian limestone after grinding in step 1) is ≥400m². 2 / kg, specifically 420m 2 / kg, 430m 2 / kg, 440m 2 / kg, 450m 2 / kg, 460m 2 / kg, 480m 2 / kg, 500m 2 / kg.

[0023] In this invention, the particle size of the raw material blank is 2~5cm, specifically 2.5cm, 3cm, 3.5cm, 4cm, or 4.5cm.

[0024] In this invention, the temperature of the first calcination in step 2) is 750~850℃, specifically 760℃, 780℃, 800℃, 820℃, or 840℃; the time is 30~60min, specifically 35min, 40min, 45min, 50min, or 55min; and the heating rate is 5~8℃ / min, specifically 5.5℃ / min, 6℃ / min, 6.5℃ / min, 7℃ / min, or 7.5℃ / min. The purpose of the first calcination is to decompose the magnesite and some calcite in the low-grade magnesian limestone to generate highly active MgO and CaO.

[0025] In this invention, the second calcination temperature is 900~1000℃, specifically 920℃, 940℃, 950℃, 960℃, or 980℃; the time is 60~120min, specifically 70min, 80min, 90min, 100min, or 110min; and the heating rate is 3~5℃ / min, specifically 3.5℃ / min, 4℃ / min, or 4.5℃ / min. During the second calcination, the composite mineralizer plays a role in promoting the solid-phase reaction between highly active MgO and CaO and SiO2 in the system, directionally generating dicalcium silicate (β-C2S), magnesium-containing dicalcium silicate ((Ca,Mg)2SiO4) solid solutions, and calcium magnesium feldspar (C2MS2), while effectively inhibiting the excessive crystallization growth of free periclase (f-MgO).

[0026] In this invention, the cooling rate of the cooling step is ≥50℃ / min, specifically 55℃ / min, 60℃ / min, 65℃ / min, 70℃ / min, 75℃ / min, or 80℃ / min. The preferred cooling method in this invention is forced air cooling to achieve rapid cooling, thereby quickly fixing the beneficial mineral phases formed at high temperatures and preventing the transformation of β-C2S into γ-C2S.

[0027] In this invention, the ambient temperature digestion in step 3) is as follows: the crushed clinker is fed into a digestion reactor and water is sprayed for digestion. This step can rapidly digest the free active MgO and CaO in the clinker into Ca(OH)2 and Mg(OH)2.

[0028] In this invention, the particle size of the crushed clinker is ≤5mm, specifically 0.5mm, 1mm, 2mm, 3mm, or 4mm.

[0029] In this invention, the mass of water sprayed during room temperature digestion is 15-30% of the total mass of MgO and CaO in the clinker, specifically 16%, 18%, 20%, 22%, 24%, 25%, 26%, and 28%.

[0030] In this invention, the heating digestion in step 3) is as follows: After digestion at room temperature, the temperature of the digestion reactor is adjusted, water is sprayed first, and after the water spraying is completed, a silica powder solution and a citrate solution are sprayed in for digestion. The purpose of spraying some water first in this step is to accelerate the digestion of residual free active MgO and CaO. The purpose of spraying silica powder and citrate is to induce the hydration of dicalcium magnesium silicate to form a gel, which preferentially forms a film on the surface of the incompletely digested MgO particles and forms a dense protective layer. Preferably, this step maintains a constant temperature throughout and is continuously stirred slowly to ensure that the gel is uniformly coated and the expansion is effectively constrained, thereby significantly improving the volume stability of the system.

[0031] In this invention, during the heated digestion, the temperature of the digestion reactor is 80~90℃, specifically 82℃, 84℃, 85℃, 86℃, or 88℃; the heated digestion is preferably carried out under stirring conditions, and the stirring rate is 10~20 r / min, specifically 12 r / min, 14 r / min, 15 r / min, 16 r / min, or 18 r / min.

[0032] In this invention, during the heated digestion, the total mass of water used is 70-105% of the total mass of MgO and CaO in the clinker, specifically 75%, 80%, 85%, 90%, 95%, or 100%; the mass of water sprayed during heated digestion is 30-40% of the total mass of water used in heated digestion, specifically 32%, 34%, 35%, 36%, or 38%; the remaining water is added in the form of silica powder solution and citrate solution.

[0033] In this invention, during the heating and digestion process, the mass ratio of the clinker to the silica powder in the silica powder solution and the citrate in the citrate solution is 100:0.1~2:0.05~0.2, preferably 100:0.5~1.5:0.08~0.15, and more preferably 100:1:0.1.

[0034] In this invention, the citrate refers to a substance containing citrate ions, preferably citric acid and / or sodium citrate.

[0035] In this invention, the relative humidity of the aging process is ≥90%, specifically 92%, 94%, 95%, 96%, 98%, or 100%; the time is 24~48h, specifically 25h, 30h, 35h, 36h, 40h, 42h, or 45h.

[0036] In this invention, the specific surface area after grinding is 430~500m². 2 / kg, specifically 440m 2 / kg, 450m 2 / kg, 460m 2 / kg, 470m 2 / kg, 480m 2 / kg, 490m 2 / kg.

[0037] The present invention also provides a magnesium-based natural hydraulic lime prepared by the above preparation method.

[0038] In this invention, the main mineral composition of the prepared magnesium-based natural hydraulic lime is: 15-45% calcium hydroxide, 2-10% magnesium hydroxide, 10-20% dicalcium silicate, 2-12% magnesium-containing dicalcium silicate, and 1-8% calcium magnesium feldspar.

[0039] In this invention, the setting time of the magnesian natural hydraulic lime meets the NHL2 or NHL5 standard, with the former having a 28-day compressive strength ≥2.0 MPa and the latter having a 28-day compressive strength ≥5.0 MPa, and the volume stability is qualified after boiling and long-term soaking tests.

[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0041] Example 1

[0042] S1: Low-grade magnesian limestone ore was selected as raw material, with the following chemical composition by mass percentage: CaO 48.86%, MgO 9.18%, SiO2 7.82%, Al2O3 0.42%, Fe2O3 0.58%, and loss on ignition 33.14%. The raw ore was crushed to a particle size of less than 5 mm using a jaw crusher, and then sieved using a vibrating screen. Particles with a particle size of 1-3 mm were used as pretreatment raw material. The crushed and sieved powder was placed in a ball mill, and a composite mineralizer was added at a mass ratio of 0.2%. The composite mineralizer was composed of borax, gypsum, and nano-titanium dioxide (Shanghai Yuanye Biotechnology Co., Ltd., CAS#13463-67-7) in a mass ratio of 3:7:0.5. The mixture was ground in the ball mill at a speed of 300 r / min for 30 min to ensure that the mineralizer and powder were fully and uniformly mixed, and the specific surface area of ​​the powder was controlled to reach 420 m². 2 / kg. The ground material is mixed with an appropriate amount of water and shaped to obtain raw material blanks with a particle size of 2~5cm, which are then placed in a sealed container for later use.

[0043] S2: The raw material blank obtained in step S1 is placed in a muffle furnace for a first calcination. First, it is heated from room temperature to 780℃ at a heating rate of 5℃ / min, and held at this temperature for 40 min to allow magnesite and some calcite to decompose, generating highly active MgO and CaO. Then, the temperature is further increased to a peak temperature of 920℃ at a heating rate of 4℃ / min and held for 80 min. During this high-temperature reconstruction stage, the composite mineralizer promotes the solid-phase reaction of highly active MgO, CaO, and SiO2, directionally generating dicalcium silicate, magnesium-containing dicalcium silicate solid solution, and calcium magnesium feldspar, while simultaneously inhibiting the excessive crystallization growth of free periclase. After calcination, the clinker is subjected to forced air cooling at a rate controlled at 55℃ / min to rapidly fix the beneficial mineral phases formed at high temperature and prevent the transformation of β-C2S to γ-C2S.

[0044] S3: The clinker obtained in S2 is crushed to a particle size of less than 5 mm using a jaw crusher. It is then fed into a horizontal dynamic digestion reactor and digested using a segmented spray water method. The theoretical water consumption is calculated to be 1.1 times the total mass of MgO and CaO, and the total water consumption is determined accordingly. First stage: 30% of the total mass of MgO and CaO is sprayed into room temperature water to rapidly digest the free active MgO and CaO in the clinker into Ca(OH)2 and Mg(OH)2. The exothermic reaction raises the system temperature. Second stage: When the reactor temperature reaches 85℃, the remaining 40% of the total water volume is first sprayed in to accelerate the digestion of residual free active MgO and CaO. Then, 0.1% of the dry weight of microsilica powder (Shanghai Yuanye Biotechnology Co., Ltd.) and 0.05% of sodium citrate are sprayed in to induce the hydration of dicalcium magnesium silicate to form a gel, which forms a film on the surface of the incompletely digested MgO particles and creates a dense protective layer. The temperature was maintained at 85±2℃ throughout the process, and the mixture was stirred slowly (15 r / min) to ensure that the gel was evenly coated and its expansion was effectively constrained.

[0045] S4: The digested material was aged for 36 hours at room temperature and 95% relative humidity to ensure uniform distribution of moisture and stress. After aging, the sample was ground in a ball mill to a specific surface area of ​​420 m². 2 / kg yields the finished product, magnesium-based natural hydraulic lime NHL2.

[0046] Example 2

[0047] S1: Low-grade magnesian limestone ore was selected as raw material, with the following chemical composition by mass percentage: CaO 48.03%, MgO 9.87%, SiO2 6.52%, Al2O3 0.60%, Fe2O3 0.63%, and loss on ignition 34.25%. The ore was crushed and sieved to obtain magnesium-rich calcium powder (1-3 mm) with uniform particle size. A composite mineralizer, comprising 0.3% by mass, was added to the powder. The composite mineralizer was prepared by compounding borax, gypsum, and nano-titanium dioxide (same as in Example 1) in a mass ratio of 4:6:0.8. After thorough mixing, the powder was further ground until the specific surface area of ​​the powder reached 430 m². 2 / kg, the ground material is mixed with an appropriate amount of water to form a raw material blank with a particle size of 2~5cm, and placed in a sealed container for later use.

[0048] S2: Place the raw material blanks obtained in step S1 into a stepped controlled kiln. Heat to 800℃ at a heating rate of 7℃ / min and hold for 50 min to decompose magnesite and some calcite. Then heat to 950℃ at a rate of 4℃ / min and hold for 90 min, where a composite mineralizer promotes the formation of the target mineral phase. After calcination, force-cool with air at a cooling rate of 60℃ / min.

[0049] S3: Crush the clinker obtained in S2 to a particle size of less than 5 mm. Feed it into a horizontal dynamic digestion reactor, with a total water volume of 1.15 times the total mass of MgO and CaO. First stage: Inject 25% of the total MgO and CaO volume of room temperature water to rapidly digest the free active MgO and CaO. Second stage: When the reactor temperature reaches 88℃, first inject 35% of the remaining total water volume, then inject 0.15% of the dry weight of silica powder (same as in Example 1) and 0.1% of citric acid. Maintain the temperature at 88±2℃ throughout the process, and continuously stir slowly (15 r / min) to ensure uniform gel coating.

[0050] S4: The digested material is aged for 48 hours at room temperature and 95% relative humidity. After aging, it is ground to a specific surface area of ​​430 m². 2 / kg yields the finished product, magnesium-based natural hydraulic lime NHL2.

[0051] Example 3

[0052] S1: Low-grade magnesian limestone ore was selected as raw material, with the following chemical composition by mass percentage: CaO 48.08%, MgO 10.30%, SiO 28.22%, Al 2O 3 0.53%, Fe 2O 3 0.41%, and loss on ignition 32.51%. The ore was crushed and sieved to obtain magnesium-rich calcium powder (1-3 mm) with uniform particle size. A composite mineralizer, comprising 0.4% by mass, was added to the powder. The composite mineralizer was prepared by compounding borax, gypsum, and nano-titanium dioxide (same as in Example 1) in a mass ratio of 4:6:0.8. After thorough mixing, the powder was further ground until the specific surface area of ​​the powder reached 450 m². 2 / kg, the ground material is mixed with an appropriate amount of water to form a raw material blank with a particle size of 2~5cm, and placed in a sealed container for later use.

[0053] S2: Place the raw material blanks obtained in step S1 into a stepped controlled kiln. Heat to 820℃ at a heating rate of 5℃ / min and hold for 60 min. Then heat to 980℃ at a rate of 3℃ / min and hold for 100 min. The composite mineralizer promotes the formation of the target mineral phase. After calcination, force-cool by air at a cooling rate of 65℃ / min.

[0054] S3: Crush the clinker obtained in S2 to a particle size of less than 5 mm. Feed it into a horizontal dynamic digestion reactor, with a total water volume of 1.2 times the total mass of MgO and CaO. First stage: Inject 20% of the total MgO and CaO volume of room temperature water to rapidly digest the free active MgO and CaO. Second stage: When the reactor temperature reaches 90℃, first inject the remaining 30% of the total water volume, then inject 0.2% of the dry weight of silica powder (same as in Example 1) and 0.15% of the dry weight of sodium citrate. Maintain the temperature at 90±2℃ throughout the process, and continuously stir slowly (15 r / min) to ensure uniform gel coating.

[0055] S4: The digested material is aged for 48 hours at room temperature and 95% relative humidity. After aging, it is ground to a specific surface area of ​​450 m². 2 / kg yields the finished product, magnesium-based natural hydraulic lime NHL2.

[0056] Example 4

[0057] S1: Low-grade magnesian limestone ore was selected as raw material, with the following chemical composition by mass percentage: CaO 45.21%, MgO 8.05%, SiO2 12.66%, Al2O3 0.82%, Fe2O3 0.28%, and loss on ignition 32.98%. The ore was crushed and sieved to obtain magnesium-rich calcium powder (1-3 mm) with uniform particle size. A composite mineralizer, comprising 0.5% by mass, was added to the powder. The composite mineralizer was prepared by compounding borax, gypsum, and nano-titanium dioxide (same as in Example 1) in a mass ratio of 4:5:1. After thorough mixing, the powder was further ground until the specific surface area of ​​the powder reached 460 m². 2 / kg, the ground material is mixed with an appropriate amount of water to form a raw material blank with a particle size of 2~5cm, and placed in a sealed container for later use.

[0058] S2: Place the raw material blanks obtained in step S1 into a stepped controlled kiln. Heat to 850℃ at a heating rate of 8℃ / min and hold for 50 min. Then heat to 1000℃ at a rate of 5℃ / min and hold for 120 min. The composite mineralizer promotes the formation of the target mineral phase. After calcination, force-cool by air at a cooling rate of 70℃ / min.

[0059] S3: Crush the clinker obtained in S2 to a particle size of less than 5 mm. Feed it into a horizontal dynamic digestion reactor, with a total water volume of 1.15 times the total mass of MgO and CaO. First stage: Inject room temperature water, accounting for 18% of the total MgO and CaO, to rapidly digest the free active MgO and CaO. Second stage: When the reactor temperature reaches 90℃, first inject the remaining 32% of the total water volume, then inject 0.5% of the dry weight of silica powder (same as in Example 1) and 0.2% of citric acid. Maintain the temperature at 90±2℃ throughout the process, and continuously stir slowly (15 r / min) to ensure uniform gel coating.

[0060] S4: The digested material is aged for 48 hours at room temperature and 95% relative humidity. After aging, it is ground to a specific surface area of ​​460 m². 2 / kg yields the finished product of magnesium-based natural hydraulic lime NHL5.

[0061] Example 5

[0062] S1: Low-grade magnesian limestone ore was selected as raw material, with the following chemical composition by mass percentage: CaO 48.57%, MgO 10.26%, SiO2 11.01%, Al2O3 0.38%, Fe2O3 0.35%, and loss on ignition 29.43%. The ore was crushed and sieved to obtain magnesium-calcium-rich powder (1-3 mm) with uniform particle size. A composite mineralizer, comprising 0.45% by mass, was added to the powder. The composite mineralizer was prepared by compounding borax, gypsum, and nano-titanium dioxide (same as in Example 1) in a mass ratio of 3:6:1. After thorough mixing, the powder was further ground until the specific surface area of ​​the powder reached 480 m². 2 / kg, the ground material is mixed with an appropriate amount of water to form a raw material blank with a particle size of 2~5cm, and placed in a sealed container for later use.

[0063] S2: Place the raw material blanks obtained in step S1 into a stepped controlled kiln. Heat to 830℃ at a heating rate of 7℃ / min and hold for 45 min. Then heat to 980℃ at a rate of 4℃ / min and hold for 110 min. The composite mineralizer promotes the formation of the target mineral phase. After calcination, force-cool by air at a cooling rate of 75℃ / min.

[0064] S3: Crush the clinker obtained in S2 to a particle size of less than 5 mm. Feed it into a horizontal dynamic digestion reactor, with a total water volume of 1.2 times the total mass of MgO and CaO. First stage: Inject 15% of the total MgO and CaO volume of room temperature water to rapidly digest the free active MgO and CaO. Second stage: When the reactor temperature reaches 85°C, first inject 35% of the remaining total water volume, then inject 0.8% of the dry weight of silica powder (same as in Example 1) and 0.15% of the dry weight of sodium citrate. Maintain the temperature at 85±2°C throughout the process, and continuously stir slowly (15 r / min) to ensure uniform gel coating.

[0065] S4: The digested material is aged for 36 hours at room temperature and 95% relative humidity. After aging, it is ground to a specific surface area of ​​480 m². 2 / kg yields the finished product of magnesium-based natural hydraulic lime NHL5.

[0066] Example 6

[0067] S1: Low-grade magnesian limestone ore was selected as raw material, with the following chemical composition by mass percentage: CaO 45.81%, MgO 10.42%, SiO2 12.85%, Al2O3 0.42%, Fe2O3 0.31%, and loss on ignition 30.19%. The ore was crushed and sieved to obtain magnesium-rich calcium powder (1-3 mm) with uniform particle size. A composite mineralizer, comprising 0.5% by mass, was added to the powder. The composite mineralizer was prepared by compounding borax, gypsum, and nano-titanium dioxide (same as in Example 1) in a mass ratio of 4:6:0.8. After thorough mixing, the powder was further ground until the specific surface area of ​​the powder reached 500 m². 2 / kg, the ground material is mixed with an appropriate amount of water to form a raw material blank with a particle size of 2~4cm, and placed in a sealed container for later use.

[0068] S2: Place the raw material blanks obtained in step S1 into a stepped controlled kiln. Heat to 850℃ at a heating rate of 8℃ / min and hold for 60 min. Then heat to 1000℃ at a rate of 5℃ / min and hold for 120 min. The composite mineralizer promotes the formation of the target mineral phase. After calcination, force-cool by air at a cooling rate of 80℃ / min.

[0069] S3: Crush the clinker obtained in S2 to a particle size of less than 5 mm. Feed it into a horizontal dynamic digestion reactor, with a total water volume of 1.2 times the total mass of MgO and CaO. First stage: Inject 15% of the total MgO and CaO volume of room temperature water to rapidly digest the free active MgO and CaO. Second stage: When the reactor temperature reaches 90℃, first inject 30% of the remaining total water volume, then inject 1.0% of the dry weight of silica powder (same as in Example 1) and 0.2% of sodium citrate. Maintain the temperature at 90±2℃ throughout the process, and continuously stir slowly (15 r / min) to ensure uniform gel coating.

[0070] S4: The digested material is aged for 48 hours at room temperature and 95% relative humidity. After aging, it is ground to a specific surface area of ​​500 m². 2 / kg yields the finished product of magnesium-based natural hydraulic lime NHL5.

[0071] Comparative Example 1 and Comparative Example 2 used NHL2 and NHL5 manufactured by Saint-Astier, France, respectively.

[0072] The setting time of the magnesium-based natural hydraulic limes prepared in Examples 1-6, NHL2 of Comparative Example 1, and NHL5 of Comparative Example 2 was determined according to GB / T 1346-2011 and BS EN 459-2.

[0073] The compressive strength of the magnesian natural hydraulic lime prepared in Examples 1-6, and NHL2 and NHL5 of Examples 1 and 2 were tested according to the test methods specified in European standards BS-EN-459 and BS-EN-196. The stability test was conducted according to GB / T 1346-2011 "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement". Specifically, 450±2g of magnesian natural hydraulic lime, 1350g±5g of standard sand, and 225g±1g of water were weighed, with a water-cement ratio of 0.5, to prepare standard specimens of 40mm×40mm×160mm. The prepared specimens were cured in a constant temperature and humidity (temperature 25℃, humidity 95%) standard curing chamber for 28 days. Various indicators of the magnesian natural hydraulic lime were measured, and the results are shown in Table 1. The main mineral phase contents of Examples 1-6 and Comparative Examples 1-2 are shown in Table 2.

[0074] Table 1 Test results of the properties of natural hydraulic lime

[0075] Table 2. Main mineral phase content of magnesian natural hydraulic lime

[0076] Table 1 shows that the 28-day compressive strength of the magnesium NHL2 samples obtained in Examples 1-3 of this invention is 2.5-2.8 MPa, the initial setting time is 545-580 min, the final setting time is 980-1123 min, and the stability is qualified. The compressive strength of the magnesium NHL2 samples in Examples 4-6 is 7.3-7.8 MPa, the initial setting time is 172-198 min, the final setting time is 411-472 min, and the stability is qualified. Compared with Comparative Example 1 (NHL2, 2.2 MPa) and Comparative Example 2 (NHL5, 5.9 MPa), the self-made samples have higher compressive strength, similar setting times that are within a reasonable range, and qualified stability, indicating that the two self-made natural hydraulic limes fully meet the standard requirements.

[0077] As can be seen from Table 2, the self-made magnesium-based natural hydraulic lime (Examples 1-6) contains significantly higher levels of magnesium hydroxide than commercially available ordinary NHL (Comparative Examples 1 and 2). It also produces magnesium-containing dicalcium silicate (1.22%-2.14%) and calcium magnesium feldspar (1.12%-1.74%), which are almost absent in ordinary NHL. These magnesium-containing mineral phases can effectively improve the strength of the material. Therefore, magnesium-based NHL is significantly superior to commercially available ordinary NHL in terms of strength and environmental adaptability.

[0078] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0079] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone through mineral phase reconstruction, characterized in that, Includes the following steps: 1) Crush low-grade magnesian limestone, mix and grind it with a composite mineralizer, and then mix it with water to form a raw material blank. 2) The raw material billet is subjected to the first calcination, the second calcination, and the cooling steps in sequence to complete the mineral phase reconstruction and obtain clinker; 3) After the clinker is crushed, it is sequentially digested at room temperature and then digested at elevated temperature to obtain the digested material; 4) The digested materials are sequentially aged and ground to obtain magnesian natural hydraulic lime; The composite mineralizer is obtained by mixing borax, gypsum and nano titanium dioxide in a mass ratio of 3~5:5~7:0.5~1; The mass ratio of low-grade magnesian limestone to composite mineralizer in step 1) is 100:0.1~0.5; In step 2), the temperature of the first calcination is 750~850℃, the time is 30~60min, and the heating rate is 5~8℃ / min; The second calcination temperature is 900~1000℃, the time is 60~120min, and the heating rate is 3~5℃ / min; The cooling rate of the cooling step is ≥50℃ / min; The ambient temperature digestion described in step 3) is as follows: the crushed clinker is fed into the digestion reactor and water is sprayed for digestion; The heating digestion described in step 3) is as follows: after the room temperature digestion is completed, the temperature of the digestion reactor is adjusted, water is sprayed first, and after the water spraying is completed, silica powder solution and citrate solution are sprayed in for digestion. In the heated digestion process, the temperature of the digestion reactor is 80~90℃.

2. The method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone through mineral phase reconstruction according to claim 1, characterized in that, The chemical composition of the low-grade magnesian limestone, by mass percentage, is as follows: CaO content 45-52%, MgO content 8-15%, SiO2 content 6-15%, calcination vector 27-35%, with the balance being impurities.

3. The method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone through mineral phase reconstruction according to claim 2, characterized in that, The specific surface area of ​​the low-grade magnesian limestone after grinding in step 1) is ≥400m². 2 / kg; The particle size of the raw material blank is 2~5cm.

4. The method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone through mineral phase reconstruction according to claim 3, characterized in that, The particle size of the clinker after crushing in step 3) is ≤5mm; The mass of water injected during room temperature digestion is 15-30% of the total mass of MgO and CaO in the clinker.

5. The method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone through mineral phase reconstruction according to claim 4, characterized in that, In step 3), during the heating and digestion process, the total mass of water used is 70-105% of the total mass of MgO and CaO in the clinker. The mass of water injected during the heated digestion process is 30-40% of the total mass of water used in the heated digestion process. In the heating digestion process, the mass ratio of clinker to silica powder in the silica powder solution and citrate in the citrate solution is 100:0.1~2:0.05~0.

2.

6. A method for preparing magnesian natural hydraulic lime from low-grade magnesian limestone through mineral phase reconstruction according to claim 4 or 5, characterized in that, The aging process is carried out at a relative humidity of ≥90% for 24~48 hours. The specific surface area after grinding is 430~500m². 2 / kg.

7. Magnesium-based natural hydraulic lime prepared by the method for preparing magnesium-based natural hydraulic lime from low-grade magnesium limestone by mineral phase reconstruction as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Magnesian natural hydraulic lime and preparation method thereof

    CN117361912A

  • Natural hydraulic lime clinker and method for preparing early-strength hydraulic lime from natural hydraulic lime clinker

    CN118479762A

  • Natural hydraulic lime and preparation method thereof

    CN113666652A

  • Modified hydraulic lime and mineralization-assisted low-temperature synthesis method thereof

    CN114702253A